KAJIAN LITERATUR: PERAN BIOAKTIVITAS SENYAWA ALKALOID SEBAGAI ANTIOKSIDAN DAN PENGARUH TOKSISITAS TERHADAP ARTEMIA SALINA - A. Febriani Putri Paramitha; Tiara Maharani; Rian Erlangga Syahputra; Alvina Meutia Anzalna; Ari Putra Wijaya Simangunsong; Usman (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Alkaloids are bioactive compounds that are widely found in plants or medicinal plants, and are known to have various pharmacological benefits, including antioxidant properties. The role of alkaloids as antioxidants to protect Artemia salina from oxidative damage. Antioxidant compounds, including alkaloids, work by capturing and neutralizing free radicals that can cause oxidative stress in organism cells. However, the potential toxicity of alkaloids in aquatic organisms, such as Artemia salina, also needs to be studied to understand the possible side effects, because these antioxidant properties function to protect cells from damage caused by free radicals. This study aims to determine the bioactivity of alkaloid compounds against plants as antioxidants and toxicity to Artemia salina. The method used in this study is SLR (Systematic Literature Review) which collects and analyzes various sources of literature related to alkaloid bioactivity compounds against plants as antioxidants and toxicity to Artemia salina. The results showed that alkaloids have significant antioxidant activity, which is indicated by their ability to neutralize free radicals. However, toxicity tests also showed that certain concentrations had significant adverse effects on the survival of Artemia salina. Keywords: Alkaloids, Antioxidants, Toxicity, Artemia salina.